Model Kolaborasi Pengelolaan Event Pariwisata Berbasis Budaya Studi: Kenduri Sko di Kota Sungai Penuh Provinsi Jambi - Seharja, Sesde; Yuniati, Nining; Damiasih, Damiasih (Universitas Batanghari Jambi, 2024)
Kenduri Sko is a culture-based tourism event that grew from the tradition of the Kerinci tribal community in Sungai Full City, this event is an ancestral heritage tradition that has been carried out for generations, the implementation of the Kenduri Sko event involves many parties, therefore good cooperation between stakeholders involved in its management is needed. This study aims to determine the model of stakeholder collaboration in the management of Kenduri Sko events. This research uses qualitative descriptive methods, the informants are elements of the Pentahelix consisting of government, academia, business, society and media. The data used are primary data and secondary data, data collection is carried out by discussion with informants through focus group discussion (FGD) forums in addition, data is also obtained from the results of literature studies on books and previous research that have relevant topics. The results of this study show that the Pentahelix collaboration model currently applied to the Kenduri Sko event has not been effective, therefore it is necessary to develop a collaboration model into Hexahelix so that governance in the implementation of Kenduri Sko can be more effective and optimal.